Government delivery system: the effectiveness of local authorities in Perak - Mohamed Osman, Mariana; Bachok, Syahriah (2014)
Innovation and transformation in service delivery are taking place around the world as governments recognize the value that can be achieved through innovation and transformation for desired policy outcomes and increased citizen trust in government. Citizens have come to expect the same level of services from government that they experience in the commercial sector. Research shows there is a strong link between quality of services and the trust and confidence citizens have in their government. Thus, some governments are adopting truly innovative practices that effect changes in service delivery to their citizens.This research aims in evaluating the performance of the service delivery by LAs in Perak. The current issues regarding service delivery by LAs in Perak were Highlighted and analyzed to recommend better strategies and action plan for improving service delivery of PBTs towards a world class status. Therefore, this research highlighted some of the project outcomes and key features of the project that would directly emphasize the focus of this research in evaluating the effectiveness of local authorities in delivering their services to the people of Perak.